Mapping the coupling between tract reachability and cortical geometry of the human brain - Li, Deying; Zalesky, Andrew; Wang, Yufan; Wang, Haiyan; Ma, Liang; Cheng, Luqi; Banaschewski, Tobias; Barker, Gareth J.; Bokde, Arun L. W.; Brühl, Rüdiger; Desrivières, Sylvane; Flor, Herta; et al. (Nature Communications, 2025)
The study of cortical geometry and connectivity is prevalent in human brain research. However, these two aspects of brain structure are usually examined separately, leaving the essential connections between the brain’s folding patterns and white matter connectivity unexplored. In this study, we aim to elucidate the fundamental links between cortical geometry and white matter tract connectivity. We develop the concept of tract-geometry coupling (TGC) by optimizing the alignment between tract connectivity to the cortex and multiscale cortical geometry. We confirm in two independent datasets that cortical geometry reliably characterizes tract reachability, and that TGC demonstrates high test-retest reliability and individual-specificity. Interestingly, low-frequency TGC is more heritable and behaviorally informative. Finally, we find that TGC can reproduce task-evoked cortical activation patterns and exhibits non-uniform maturation during youth. Collectively, our study provides an approach to mapping cortical geometry-connectivity coupling, highlighting how these two aspects jointly shape the connected brain.
Gesehen am 06.11.2025
Mitglieder des IMAGEN Consortium: Tobias Banaschewski, Gareth J. Barker, Arun L.W. Bokde, Rüdiger Brühl, Sylvane Desrivières, Herta Flor, Hugh Garavan, Penny Gowland, Antoine Grigis, Andreas Heinz, Hervé Lemaître, Jean-Luc Martinot, Marie-Laure Paillère Martinot Eric Artiges, Frauke Nees, Dimitri Papadopoulos Orfanos, Luise Poustka, Michael N. Smolka, Nilakshi Vaidya, Henrik Walter, Robert Whelan, Gunter Schumann & Tianye Jia